Forest as a Redeemer: Experiences Drawn from Selected Rural Ejagham Communities in Etung Local Government Area of Cross River State, Nigeria - F. I, Okpiliya; P.O, Oka; J, Mbu (Review of Environment and Earth Sciences, 2016)
The role of forest in sustaining the lives of man generally cannot be over-emphasised. Generally, forest provides opportunities for food, shelter, trado-medical services, ecological services and income. The objective of this study is to evaluate the role of forest resources in the provision of food for the people of Etung in Cross River State. Six communities were chosen for the study. They include, Abia, Agbokim, Ajassor, Abijang, Etomi and Nsofang. One thousand, nine hundred copies of questionnaires were distributed to household heads in the study area. The student ‘t’ test was used to test for the seasonal variation in the number of persons involved in the exploitation and utilization of forest resources. The result of the study indicated that forest is a major source of food as it provides mushrooms, seed and spices, fruits, vegetables and a great variety of animals for the people of Etung. Also income generated in the area ranged from N10,000 to over N100,000 during the dry and rainy seasons. The student ‘t’ test analysis for the variation in the level of involvement of the people in the exploitation and utilization of forest resources revealed that there was significant seasonal variation in the level of involvement of the people of Etung in only two forest resources – medicinal plants, (t(1938) = 3.416, P<.05) and leafy vegetables, -(1938) =3.335, P<0.05). On the other hand the number of people involved in the exploitation of the other nine forest resources was not significant.